A graphic representation of Hutchinson's phylogenetic system - Rodríguez C., Rafael L. (1956)
In HUTCHINSON'S publications, as well as in BARKLEY'S (1) and LAWRENCE'S (ID, p. 137), diagrams are presented showing as linear sequences his concept of the relationships of the various orders or families. HUTCHINSON (7, p. 649) stressed the fact that such a diagram... is not intended to convey the idea that families are derived from each other as they exist at the present time, but that one or more have been derived from the same basal stock as the one lower down in the family 'tree'. The possibility of confusion of these two completely different concepts has been pointed out by BARKLEY (op. cit) and by RODRÍGUEZ (11), the latter with reference to BESSEY'S ( 2) familiar "cactus plant" illustration of his own phylogenetic treatment of the Angiosperms. Both authors pointed out that a phylogenetic diagram should be thought of as a cross-section of the "family tree", made at a particular moment in time -i.e., the present- rather than as a "family tree" in itself.